Penerapan Prinsip Etika Profesi Akuntan dalam Situasi Dugaan Pelanggaran Integritas di PT Kimia Farma Tbk Tahun 2025 - Rafi Evan Wijaya; Daniel Satrio Prakoso; Eka Triana Sulistyaningsih; Rafa Putri Adara; Yunira Az Zahra Amanda Arynova; Yanuar Ramadhan (Pusat Riset dan Inovasi Nasional, 2026)
The alleged financial statement manipulation case involving PT Kimia Farma Tbk (KAEF) and its subsidiaries in 2025 has once again highlighted the importance of implementing accounting professional ethics in Indonesia. As a state-owned pharmaceutical company with significant social responsibilities, any indication of irregularities in the presentation of financial statements raises serious questions about the integrity, objectivity, and professionalism of accountants. This study aims to analyze potential violations and challenges in implementing accounting professional ethics in the Kimia Farma 2025 case, which is still under investigation. The research method used is a descriptive qualitative approach using secondary data in the form of company financial statements, credible online media publications, and the Indonesian Accountants Code of Ethics. The analysis results indicate performance pressure, conflicts of interest, and weak internal controls that can pose risks to the implementation of the principles of integrity and objectivity of accountants. However, because the investigation process is not yet complete, this study does not intend to draw legal conclusions, but rather to provide an understanding of how the principles of professional ethics are tested in situations of corporate uncertainty. The findings of this study are expected to contribute to strengthening ethical awareness, transparency, and accountability of the accounting profession, particularly in the environment of state-owned companies with high public interest.